Patient Selection Criteria for Endovascular Aortic Aneurysm Repair: Optimizing Outcomes - Taragjini, Christina; Schiro, Brian; Bemd, Bente A. T. van den; Pena, Constantino S. (Seminars in Interventional Radiology, 2024)
Endovascular aortic aneurysm repair (EVAR) has become the preferred treatment for abdominal aortic aneurysms, offering a minimally invasive alternative to open surgery. However, successful outcomes depend on meticulous patient selection. This review explores the key criteria for patient eligibility, including aneurysm size, morphology, and the quality of the proximal and distal aneurysm necks. Additionally, imaging assessment and various device variables, including anatomical suitability, are examined to emphasize their influence on procedural success. As EVAR technology evolves, understanding the nuances of patient selection remains crucial for maximizing technical success and clinical outcomes, while minimizing complications including endoleaks and migration, and extending the benefits of the procedure to a broader range of patients.
Keywords: endovascular aortic aneurysm repair; aortic aneurysm; endoleaks; abdominal aortic aneurysm